Assessing administrative service quality in higher education: development of an attribute-based framework (HEADSQUAL) in a Brazilian University. Issue 9 (2nd September 2021) - Steppacher, Damian; Cannarozzo Tinoco, Maria Auxiliadora; Caten, Carla Schewengber ten; Marcon, Arthur
ABSTRACT : This paper proposed a valid and reliable perceived quality assessment framework of administrative services in Higher Education Institutions (HEI) in the Brazilian context. The method was in two main stages: (i) map a set of quality attributes and dimensions for administrative services in HEI, (ii) build and test the perceived quality assessment framework and data collection instrument of the administrative services in a HEI. The theoretical contributions of this manuscript were the differentiated scope with a focus on administrative services in HEI, since most of the previous research addresses the area of education (final service), and the development of a specific framework for assessing administrative service quality. The managerial implication highlight was that this study can be reapplied to other HEI to improve existing services quality assessment and control instruments. Adopting the proposed structure, the HEI could promote improvements in administrative services quality and advance in the quest for excellence.